Pemanfaatan Limbah Minyak Jelantah sebagai Bahan Baku Lilin Aromaterapi di Desa Tlogo, Tretep, Kabupaten Temanggung - Fatkhurrohman, Fuad; Nuraeni, Lulu; Fioni, Alya; Adiyanti, Regita Cahya; Lutfi, Muhammad Riyatul (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Introduction: Aromatherapy is a method of treatment through the medium of odors originating from certain plant materials. Aromatherapy is often combined with alternative medicine practices and beliefs that have existed for many years. Objective: The aim of this community service activity is to present one of the business opportunities that can be carried out on an independent small and medium scale with quite promising opportunities at the moment, namely the use of used cooking oil as raw material for aromatherapy candles. Method: This activity will be attended by PKK members of Tlogo Village, Tretep District, Temanggung Regency. This activity was attended by 30 mothers using lectures, discussions and direct practice in making aromatherapy candles from used cooking oil. Result: The use of used cooking oil will pollute the environment. One way to use used cooking oil is to use it as a basic ingredient for aromatherapy candles. This utilization will indirectly reduce waste, produce aromatherapy candle products that are the same as those on the market and improve the economy of the target community. Conclusion: This community service activity encourages inmates to understand the training material and have direct discussions which create and motivate them to practice making aromatherapy candles, and are motivated to become entrepreneurs.